2012
DOI: 10.1039/c2ob06966k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the alkali degradation of (6–4) photoproduct-containing DNA

Abstract: The (6-4) photoproduct is one of the major damaged bases produced by ultraviolet light in DNA. This lesion is known to be alkali-labile, and strand breaks occur at its sites when UV-irradiated DNA is treated with hot alkali. We have analyzed the product obtained by the alkali treatment of a dinucleoside monophosphate containing the (6-4) photoproduct, by HPLC, NMR spectroscopy, and mass spectrometry. We previously found that the N3-C4 bond of the 5' component was hydrolyzed by a mild alkali treatment, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…70 This induced strand cleavage offers a functional assay for the analysis of 6-4PP formed in the genomic DNA, 71 although some studies question whether 6-4PP is truly alkaline labile. 72,73 It was reported previously that alkaline treatment of 6-4PP results in a similar hydration product possible via the gem-diol intermediate at the C4 followed by rupture of the N3-C4 bond. 72,74 Our group, however, demonstrated that the 6-4PP hydrate may not be stable enough to be detected as it undergoes a rapid esterification reaction facilitated by the 5-OH group, resulting in a stable 2-oxazolidinone (5-4) pyrimidone product after eliminating a molecule of ammonia (Scheme 10).…”
Section: Understanding the Chemical Stability Of 6-4ppmentioning
confidence: 93%
“…70 This induced strand cleavage offers a functional assay for the analysis of 6-4PP formed in the genomic DNA, 71 although some studies question whether 6-4PP is truly alkaline labile. 72,73 It was reported previously that alkaline treatment of 6-4PP results in a similar hydration product possible via the gem-diol intermediate at the C4 followed by rupture of the N3-C4 bond. 72,74 Our group, however, demonstrated that the 6-4PP hydrate may not be stable enough to be detected as it undergoes a rapid esterification reaction facilitated by the 5-OH group, resulting in a stable 2-oxazolidinone (5-4) pyrimidone product after eliminating a molecule of ammonia (Scheme 10).…”
Section: Understanding the Chemical Stability Of 6-4ppmentioning
confidence: 93%
“…The small mass difference (∼0.02 amu) due to the involvement of various isotopes can be readily resolved by high-resolution mass spectrometry. 22 This observation further suggests that 1 is formed by hydrolysis of 6-4PP (+ 18 amu due to the added water) followed by loss of an ammonia (− 18 amu due to the loss of 15 NH 3 ).…”
mentioning
confidence: 97%
“…Typically, a mass of 17 amu corresponds to an ammonia molecule; we thus wonder whether the amino moiety attached to the C2O at the 5′-thymine of the hydrolysis product has been removed. To test this hypothesis, we first incorporated a 15 N label at the N3 position via a N-nitration reaction of the uridine residue 23 and synthesized a dinucleotide TpT with the 5′-thymine containing the 15 N label. The corresponding 6-4PP was then prepared photochemically as described above.…”
mentioning
confidence: 99%
See 2 more Smart Citations